2011
DOI: 10.1113/jphysiol.2010.197723
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle fatigue precedes the slow component of oxygen uptake kinetics during exercise in humans

Abstract: Non-technical summary The mechanisms determining exercise intolerance are poorly understood. A reduction in work efficiency in the form of an additional energy cost and oxygen requirement occurs during high-intensity exercise and contributes to exercise limitation. Muscle fatigue and subsequent recruitment of poorly efficient muscle fibres has been proposed to mediate this decline. These data demonstrate in humans, that muscle fatigue, generated in the initial minutes of exercise, is correlated with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
100
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 60 publications
9
100
4
Order By: Relevance
“…This slow component of VO2 kinetics during "very heavy" exercise has been well documented, and progressive motor unit recmitment has been proposed as a potential underlying cause (e.g., Poole et al [26]). Recent findings suggest that a reduction of mechanical efficiency of early recmited motor units may also contribute to the steady rise in VO2 (6). This is in line with data from isolated frog fibers showing reduced force production relative to oxygen consumption when slowly fatiguing fibers were fatigued (18).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…This slow component of VO2 kinetics during "very heavy" exercise has been well documented, and progressive motor unit recmitment has been proposed as a potential underlying cause (e.g., Poole et al [26]). Recent findings suggest that a reduction of mechanical efficiency of early recmited motor units may also contribute to the steady rise in VO2 (6). This is in line with data from isolated frog fibers showing reduced force production relative to oxygen consumption when slowly fatiguing fibers were fatigued (18).…”
supporting
confidence: 50%
“…Although great care should be taken to interpret changes in rsEMG in terms of motor unit recmitment and rate coding (14) when rsEMG does increase, it is usually paralleled by additional motor unit recmitment and/ or increased rate coding (10,19). It is important to note that recent findings support the idea that reduced efficiency of early recmited motor units may also contribute to the rise in oxygen consumption during very heavy exercise (6,18). The concurrent decrease in mean power frequency during contractions above fatigue threshold may relate to decreases in muscle flber action potential conduction velocity, which, in tum, have been linked to fatigue-related metabolic changes such as accumulation of potassium and decreased pH (33).…”
Section: Discussionmentioning
confidence: 93%
“…The _ VO 2 slow component reflects an increase in the O 2 cost of supra-VT exercise, and thus a reduction in work efficiency, that may be attributed to the recruitment of additional (mostly type II, i.e. less efficient) muscle fibres or to a reduction in the efficiency of the working fibres (Barstow et al 1996;Cannon et al 2011;Pringle et al 2003). A reduction in the amplitude of the _ VO 2 slow component would both signify an improved exercise economy/efficiency, and be influenced by the elevation of the VT.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected. One possible speculation is that the body retained the adaptation that caused it to use more oxygen during DEC, possibly an altered recruitment of different skeletal muscle fibre types, during the INC F 79. Indeed, a recent study80 showed that a progressive increase in VO 2 , the so-called slow-component phase, can occur during an all-out 3-min cycling protocol despite decreasing levels of muscle electromyographic activity and power output throughout the trial.…”
Section: Discussionmentioning
confidence: 99%